Investigation and Analysis of Electrical Faults in the Seven-phase Induction Machine - Iffouzar, Koussaila; Roubache, Lazhar; Benachour, Ali (Periodica polytechnica. Electrical engineering and computer science, 2025)
Multiphase induction machines have revolutionized the propulsion and traction sector, thanks to their fault tolerance. This paper is focused on the analysis of electrical faults in the squirrel cage Seven-Phase Induction Machine (SPIM). This study provides a solid basis for diagnosing various faults by analyzing their distinct signatures for the electric faults that can affect this machine. To this end, a transient finite element model is elaborated to study these several electrical faults in SPIM. This paper will be devoted to the study of opening faults in various stator phases (one phase, two adjacent phases, two non-adjacent phases and two far phases), and shortcircuiting between turns of stator phases (5%, 10%, 15% of the first phase). An analysis of electromagnetic torque ripple, joule loss and efficiency is undertaken in this paper.